PENGARUH KREATIVITAS GURU TERHADAP PRESTASI BELAJAR PESERTA DIDIK MATA PELAJARAN MATEMATIKA - Rofiatun Nisa’; Sukiyanto; Latifatul Mujtahidah (CENDEKIA, 2019)
The purpose of this study was to: determine the level of teacher creativity in teaching, the level of student learning achievement, the effect of teacher creativity on student achievement in mathematics class V at MI Thoriqotul Hidayah Centini. This study uses a quantitative approach with a sample of 24 students. Data collection techniques using questionnaires and documentation. Data analysis techniques include descriptive analysis, simple linear regression analysis, t test and coefficient of determination. The results showed that the creativity of teachers was classified as moderate with a percentage of 87.5%. It meant that the teacher was quite creative in providing ideas that could make students motivated to learn, the learning achievement of class V students was moderate with a percentage of 50%. This means that students have been able to show changes including their ability to think and their skills in mathematics, from the results of t test regression analysis obtained > (3,438 > 1,717) then Ha is accepted and it can be concluded that partially the teacher creativity variable has a significant effect towards student learning achievement means the better the teacher's creativity the better the student's learning achievement.